The importance of size in private equity: Evidence from a survey of limited partners - Da Rin, Marco; Phalippou, Ludovic (Journal of Financial Intermediation, 2017)
Using a comprehensive survey, we show that investors with a larger capital allocation to private equity are more specialized−measured by the degree to which the investor focuses on private equity rather than other classes of investments−and have a wider scope of due diligence and investment activities. Other investor characteristics (experience, type, location, compensation structure, number of funds under management) play no role. In particular, endowments are not special according to the survey measures. These results are consistent with the changing LP–GP relationship in private equity as capital is increasingly concentrated in the hands of large investors.